The process of dehospitalization from the perspective of patients with long-term chronic diseases admitted to a university hospital (Research, Society and Development, 2021)
Objective: To describe the dehospitalization process from the perspective of patients with long-term chronic diseases admitted to a university hospital. Methodology: This is a qualitative research carried out in the Adult Clinical Care Unit of a University Hospital in northeastern Brazil, from August to September 2017. Results: From the data analysis three categories emerged: socioeconomic and clinical aspects that interfere in the process of de-hospitalization of chronic patients; difficulties faced during the process of de-hospitalization of chronic patients in discharge conditions and; proposals for carrying out dehospitalization. Conclusion: As coping strategies for the difficulties encountered, one should (re)know the user, caregiver and family, identify difficulties and seek ways to overcome them effectively and creatively. For this to occur, the support and articulation of other services in the health care network is essential to guarantee the proper monitoring of this user/family and continuity of safe care.